PSYCHOLOGICAL HEALTH IN THE CONTEXT OF ECONOMIC BEHAVIOR: THEORETICAL REVIEW OF THE PROBLEM - Жарікова, Світлана Борисівна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2020)
The article presents a theoretical overview of the problem of psychological health in the context of economic behavior. It is stated that the relevance, theoretical and practical significance of the problem of psychological health is confirmed in numerous researches of modern scientists, which allows to mark it as one of the priority among the developed psychological problems. In the context of constant socio-economic changes, the problem of the psychological health of the personality becomes of particular importance. Economic changes, which is one of the components of the transformation processes that take place in Ukrainian society, set the specific environmental context of the functioning of the psychological health of a personality. The content of "psychological health" concept and its criteria are considered. The following approaches to understanding this phenomenon are indicated: socio-psychological, ontogenetic, professional, moral-psychological, general-psychological and resource. It is stated that scientists clearly define such a perspective of psychological health functioning as the optimality and constructiveness of interaction with the environment and the world as a whole, which makes it possible to consider adequate economic behavior as one of the aspects of such interaction. The analysis of the concept of "economic behavior" in terms of economic and psychological science, as well as its types such as financial behavior, conservation behavior, debt behavior, investment behavior, "poverty behavior" is presented. On the basis of the analysis of modern theoretical and empirical researches the connection of psychological health and economic behavior is determined, the contribution of a number of psychological characteristics to the functioning of different types of economic behavior is revealed. It is noted that the economic side of life of a modern person living in a transformational society is one of the significant variables in the formation of psychological health, the condition of which, in this context, is economic behavior that is adequate to the ongoing and predicted changes.